2022
DOI: 10.1111/eje.12849
|View full text |Cite
|
Sign up to set email alerts
|

Oral potentially malignant disorders – An assessment of knowledge and attitude to future education in undergraduate dental students

Abstract: Introduction The aim of this study was to assess the knowledge and clinical experience of oral potentially malignant disorders (OPMDs) in undergraduate dental students in six European countries (Croatia, France, Italy, Portugal, Spain and United Kingdom) and assess student’s attitude and preference to future education on the topic. A secondary aim was to identify gaps in student’s knowledge and clinical practice. The study was a part of the Erasmus+ project “Oral Potentially Malignant Disorders: Healthcare Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nonetheless, they may need more clinical skills to apply this knowledge in real clinical settings, especially because attending CPD modules in oral medicine did not improve their diagnostic skills. It has been reported that educational intervention based on real clinical scenarios significantly improves general dental practitioners' ability to recognise OPMDs (Brailo et al, 2022; Gaballah & Kujan, 2022). This is consistent with our findings, where the capability of the dental students in diagnosing OPMDs and oral malignant lesions improved significantly after exposure to clinical cases in oral medicine clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they may need more clinical skills to apply this knowledge in real clinical settings, especially because attending CPD modules in oral medicine did not improve their diagnostic skills. It has been reported that educational intervention based on real clinical scenarios significantly improves general dental practitioners' ability to recognise OPMDs (Brailo et al, 2022; Gaballah & Kujan, 2022). This is consistent with our findings, where the capability of the dental students in diagnosing OPMDs and oral malignant lesions improved significantly after exposure to clinical cases in oral medicine clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The authors pointed out that the proportion of students who have observed a biopsy of an oral lesion was 82%, assisted with a biopsy of an oral lesion was 76%, and performed a biopsy of an oral lesion was 42%, although this percentage varied significantly between countries. The majority of students were interested in future education on OPMDs, preferably via short educational videos (Brailo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The majority focus on diagnosis alone and use outdated guidance, with little discussion on the management of these conditions. A recent study aimed at final year dental students across several European universities has demonstrated students were open to further education on OPMDs [5]. Working collaboratively with partner universities, an e-learning tool was developed, which can be easily accessed by both general medical and dental practitioners.…”
mentioning
confidence: 99%